Dor cervical e uso de dispositivos eletrônicos em universitários: prevalência e fatores associados - Candido, Jose Paulo (2018)
INTRODUCTION: Neck pain is common in several age groups of both sexes, being a second major cause on the spine, being behind reports of low back pain. OBJECTIVES: To verify the prevalence of cervical pain in university students and to associate it with demographic factors and the use of electronic devices. METHODS: A cross-sectional observational study was carried out, with 1.143 university students, from september to november 2016, using the following instruments in the interviews: a questionnaire to characterize the participants (sociodemographic aspects and use electronic devices) and, finally, the Nordic questionnaire. RESULTS: Descriptive, bivariate and Poisson regression were performed. The prevalence of neck pain was 66.7% (CI 63.8 to 69.3), and 57.6% (CI 52.9 to 62.1) were men and 72.3% (CI 68.8 to 79.4) women. The frequency of up to two days of neck pain was 42.4% in men and 45.0% in women. Regarding the duration, 36.7% of the men and 48.7% of the women said they felt the symptom less than 3 months ago. Regarding cervical pain intensity, 35.3% of men and 47.3% of women reported weak to moderate degrees of severity. In the adjusted analysis, be female (PR = 1.92, 1.49 – 2.47), watch TV for three or more hours a day (PR = 1.35, 1.05 – 1.79), use the computer for three or more hours a day (PR = 1.41, 1.08 – 1.85), use video games for three or more hours a day (PR = 1.42, 1.02 – 1.97), distance from the eye on the tablet screen of 20 cm or more (PR = 1.08, 1.01 – 1.17), posture lying on the cell phone (PR = 1.67, 1.04 – 1.72), (PR = 1.28, 1.02 –1.65), sitting posture in the use of the tablet (RP = 1.54, 1.03 – 2.38), posture lying in use of the tablet (PR = 1.83, 1.05 – 3.18) and to use the tablet for two or more hours a day (PR = 2.28, 1.15 – 4.49) remained associated with neck pain. CONCLUSION: The present study revealed a high prevalence of cervical pain and marked association with the female sex and with the variables related to the use of electronic devices, thus reinforcing the need for studies that address this type of symptom, focusing on the improvement of knowledge and in the elaboration of strategies of prevention and /or intervention, which is paramount for public health policies.